Reporting Synechocryptus bovei (Brullé, 1846) (Hymenoptera: Ichneumonidae: Cryptinae) first time in Iraq. Issue 1 (August 2020) - Al-Zurfi, Sienaa M.; Aljaafari, Raad K.; Manar,; Abbas, A.; Kareem, Ali A.
Abstract: The subfamily Cryptinae (Hymenoptera: Ichneumonidae) is the largest ichneumon wasps. During insect survey in fruit trees field, Karbala Governorate, Synechocryptus bovei was collected in 2019 using sweep nets. This is the first report of S. bovei from Karbala, Iraq.